Dopamine Receptor D5 Signaling Plays a Dual Role in Experimental Autoimmune Encephalomyelitis Potentiating Th17-Mediated Immunity and Favoring Suppressive Activity of Regulatory T-Cells - Osorio-Barrios, Francisco; Prado, Carolina; Contreras, Francisco; Pacheco, Rodrigo (Frontiers in Cellular Neuroscience, 2018)
A number of studies have shown pharmacologic evidence indicating that stimulation of type I dopamine receptor (DRs), favours T-helper-17 (Th17)-mediated immunity involved in experimental autoimmune encephalomyelitis (EAE) and in some other inflammatory disorders. Nevertheless, the lack of drugs that might discriminate between DRD1 and DRD5 has made the pharmacological distinction between the two receptors difficult. We have previously shown genetic evidence demonstrating a relevant role of DRD5-signalling in dendritic cells (DCs) favouring the CD4+ T-cell-driven inflammation in EAE. However, the role of DRD5-signalling confined to CD4+ T-cells in the development of EAE is still unknown. Here, we analysed the functional role of DRD5-signalling in CD4+ T-cell-mediated responses and its relevance in EAE by using a genetic approach. Our results show that DRD5-signalling confined to naive CD4+ T-cells exerts a pro-inflammatory effect promoting the development of EAE with a stronger disease severity. This pro-inflammatory effect observed for DRD5-signalling in naive CD4+ T-cells was related with an exacerbated proliferation in response to T-cell activation and to an increased ability to differentiate toward the Th17 inflammatory phenotype. On the other hand, quite unexpected, our results show that DRD5-signalling confined to Tregs strengthens their suppressive activity, thereby dampening the development of EAE manifestation. This anti-inflammatory effect of DRD5-signalling in Tregs was associated with a selective increase in the expression of glucocorticoid-induced tumour necrosis factor receptor-related protein (GITR), which has been described to play a critical role in the expansion of Tregs. Our findings here indicate a complex role for DRD5-signalling in CD4+ T-cells-driven responses potentiating early inflammation mediated by effector T-cells in EAE, but exacerbating suppressive activity in Tregs and thereby dampening disease manifestation in late EAE stages.